ANALISIS PENGARUH FAKTOR INTERNAL BANK TERHADAP NON PERFORMING LOAN BERDASARKAN GENERALIZED METHOD OF MOMENT - Muhammad Samsul Maryandi; Rizal Yaya; Edi Supriyono (Jurnal Keuangan dan Perbankan, 2016)
This research aims at finding out the effect of bank internal factor towards Non-Performing Loan (NPL). The internal factors of bank used in this study cover credit expansion level, operational efficiency level, credit interest level, and the percentage of credit with problems in the previous period as dynamic effect. The research was very important to conduct considering in some recent periods, the ratio of NPL owned by the bank group tend to show an increase. If compared to some previous research (especially the research that took the study case in Indonesia), this study had some strengths such as the sample used was relatively bigger in number (used 97 banks as sample during quarterly period II of 2013 until quarterly period II of 2015) and the use of Generalized Method of Moment Model to analyze the effect of bank internal factor towards NPL. Based on the analysis result of Generalized Method of Moment, it could be concluded that the level of credit expansion, operational efficiency, credit interest and the percentage of credit with problems in one previous period individually gave positive effect towards NPL. Meanwhile, the percentage of credit with problems in two previous periods gave negative effect towards NPL.